2002
DOI: 10.1021/jp014594j
|View full text |Cite
|
Sign up to set email alerts
|

LIF and IR Dip Spectra of Jet-Cooled p-Aminophenol−M (M = CO, N2): Hydrogen-Bonded or Van der Waals-Bonded Structure?

Abstract: Intermolecular interaction and stable structures of the p-aminophenol−M (M=CO, N2) 1:1 complexes have been studied by measuring the S1 ← S0 (ππ*) fluorescence excitation spectra and the IR dip spectra in the OH and NH stretch region combined with ab initio calculations. The S1−S0 electronic origin of the CO complex is 141 cm-1 red shifted from the origin of the monomer. The red shift for the CO complex is smaller than 153 cm-1 for the N2 complex, although the molecular polarizability of carbon monoxide is larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The geometry in the D 0 state may be very different from that in the S 1 state as suggested by theoretical calculations. 5…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometry in the D 0 state may be very different from that in the S 1 state as suggested by theoretical calculations. 5…”
Section: Resultsmentioning
confidence: 99%
“…1,2 We have investigated the effect of substitution of two functional groups into an aromatic ring on hydrogen-bonding interaction. [3][4][5][6] In our previous study on the 4-aminobenzonitrile (4ABN)-H 2 O complex, we have shown that the introduction of two functional groups, an amino group and a cyano group, remarkably changes stable structures of the hydrogen-bonded complex through the measurement of the IR-dip and IR-UV hole-burning spectra. 3,4 We have clearly identified three structural isomers for the 4ABN-H 2 O 1 : 1 complex.…”
Section: Introductionmentioning
confidence: 99%
“…Ltd., and was used without further purification. The experimental apparatus for the measurement of the FE and dispersed fluorescence (DF) spectra was essentially the same as that reported previously [15,16]. Briefly, 9MA was vaporized by heating the solid sample in a nozzle housing to 100-120°C.…”
Section: Methodsmentioning
confidence: 99%
“…The LIF and IR dip spectra of the latter were also interpreted on the basis of van der Waals bound structure. 20 For the most stable isomer a D e ) 787 cm -1 value was estimated at the MP2/cc-pVDZ level. Thus relatively strong binding is found in clusters with the nitrogen ligand bound to the aromatic ring, but with an additional polar substituent being present.…”
Section: Discussionmentioning
confidence: 99%
“…For phenol clusters a preference for H-bonded N 2 was found, as evident from the red shift of the S 1 ← S 0 transition and the observed red shift in the frequency of the O−H stretching vibration. Subsequent rotationally resolved measurements confirmed this assumption and resulted in good agreement between experimental data and ab initio calculations. On the other hand, clusters of less acidic chromophores offering two binding sites with nitrogen, such as aniline, ethylaniline, and aminophenol, were shown to be van der Waals bound.…”
Section: Introductionmentioning
confidence: 99%